AS INTERFACES DA PROMOÇÃO DA SAÚDE E UM PROGRAMA DE APRENDIZAGEM PROFISSIONAL - Allegretti, Maitê Menegazzo (2009)
The work with teenagers, the idea being to promote their health, as well as their healthy development through spaces that meet their needs also have been the responsibility of social organizations. Especially when it is intended to prepare for the world of work, but with a broader proposal, or as a preparation for their relations in life, by the passage of a process of learning, development, through the construction of significant actions to life. This is the proposal of the Centro de Orientação ao Adolescente de Campinas - COMEC , nongovernmental organization, with a "Programa de Aprendizagem Profissional - PAP." Such being the case , this research have with objective to characterize, by means of records , a sample of 280 adolescents , understand the perception their into the I sue lively and identify the prospects on admission and when they leave the program PAP. The study participants are adolescents from 14 to 17 years, female and male, the elementary and high school (7 th grade to 3rd grade). The forms were filled in three times. First when the teenager involved in the selection to join the program. Second when he began the work in the company and the end of the contract with the adolescent program. The results obtained through the records of the adolescents showed that the perception they have about the program is positive. They understand feelings of fear, insecurity, happiness and wishes with regard to activities that prepare them for inclusion in the formal labor market and show how this monitoring program allows for another look at the inclusion of adolescents. While the youth work is not the solution to the economic needs of many families, the educational work has been seen as a way to let the adolescent experience their first experience of working with their condition of a person in development. But it is undeniable that in some cases, they contribute significantly to the budget of the family.(AU)